The Behavior of Pulmonary Tuberculosis Patients With The Occurrence of Pulmonary Tuberculosis Transmission in the Family at Working Area Prambon Health Center Nganjuk Regency - Erni Tri Indarti; Rystika Angga Sari (STRADA : Jurnal Ilmiah Kesehatan, 2021)
Pulmonary tuberculosis can be transmitted to anyone, especially members of the family who have a history of direct contact with patient. The tranmission in the family can be terminated if the patient has practiced good prevention of transmission. The purpose was determine relationship of Behavior of Patients with The Occurrence of Pulmonary tuberculosis Transmission in the Family. Study design is a correlation with a cross sectional approach. The research was conducted on 27 February-14 March 2020. The population were 54 patients pulmonary tuberculosis. Samples were 39 respondents taken by purposive sampling. Data Collecction using a questionnaire. Data analysis using the Coefficient Contingency with α = (0,05). The Coefficient Contingency test results p-value = 0,000 ≤ α = (0,05) and relationship The Behavior of Pulmonary tuberculosis Patients with The Occurrence of Pulmonary tuberculosis Transmission in the Family. Good prevention behavior plays an important role in breaking the chain of transmission.